INSTITUTIONAL POLICIES ON ARTIFICIAL INTELLIGENCE IN UNIVERSITY LEARNING, TEACHING AND RESEARCH - Oleksandr V. Spivakovsky; Serhii A. Omelchuk; Vitaliy V. Kobets; Nataliia V. Valko; Daria S. Malchykova (Інформаційні технології і засоби навчання)
Generative artificial intelligence is rapidly transforming the educational process and the scientific work of students, lecturers, researchers and administrators of higher education institutions. There are limited and contradictory recommendations for the use of artificial intelligence in the educational process and in the educational programmes of higher education institutions. To define the scope of AI application, there is a need to develop institutional policies for higher education institutions, which will allow the academic community to determine the appropriate scope of AI application in the educational process and prevent the use of AI in areas where ethical norms are violated. The purpose of the article is to summarise and systematise the experience of forming institutional policies for the application of artificial intelligence in education, training and research in higher education institutions using the experience of Kherson State University.